Myxomycetes associated with Avicennia germinans and Laguncularia racemosa in a mangrove of El Salvador - Morales-Hernández, Ricardo; Rojas-Alvarado, Carlos (Revista Minerva, 2023)
Studies of myxomycetes in mangroves are not common and have mainly been carried out in Brazil. This study represents the first evaluation of myxomycetes associated with two mangrove plants in El Salvador, and by extension, in Central America. For this, dead plant material was collected, and the microorganisms were isolated using the moist chamber technique. The total effort of 60 samples yielded 17 species of myxomycetes, from which 11 had not previously been communicated for such ecosystems, worldwide, based on the literature. These results were relevant and showed that even though the presence of myxomycetes in mangroves was previously known, their diversity is still poorly documented. Results also demonstrated that Central American mangroves host a different assemblage than South American ones. More studies in Central America are required to test the underlying reasons.